2009
DOI: 10.1186/1755-8794-2-15
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of microRNA levels during hypoxia with predicted target mRNAs through genome-wide microarray analysis

Abstract: Background: Low levels of oxygen in tissues, seen in situations such as chronic lung disease, necrotic tumors, and high altitude exposures, initiate a signaling pathway that results in active transcription of genes possessing a hypoxia response element (HRE). The aim of this study was to investigate whether a change in miRNA expression following hypoxia could account for changes in the cellular transcriptome based on currently available miRNA target prediction tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 46 publications
4
56
0
Order By: Relevance
“…In most cases, the number of induced DEGs exceeded the number of reduced DEGs; however, the number of reduced DEGs was greater when treatment duration was extended. Most animal data sets identified fewer than 100 DEGs, with the exception of stagnant human cell cultures (more than 1,000 DEGs; Guimbellot et al, 2009). DEG numbers in microorganisms were similar to those of animals, despite their lower gene contents.…”
Section: Data Collection and Identification Of Differentially Expressmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, the number of induced DEGs exceeded the number of reduced DEGs; however, the number of reduced DEGs was greater when treatment duration was extended. Most animal data sets identified fewer than 100 DEGs, with the exception of stagnant human cell cultures (more than 1,000 DEGs; Guimbellot et al, 2009). DEG numbers in microorganisms were similar to those of animals, despite their lower gene contents.…”
Section: Data Collection and Identification Of Differentially Expressmentioning
confidence: 99%
“…Low-oxygen response expression data were obtained for 21 organisms from databases and publications: Arabidopsis (Arabidopsis thaliana; BrancoPrice et al, 2008;van Dongen et al, 2009;Mustroph et al, 2009), rice (Oryza sativa; Lasanthi- Kudahettige et al, 2007;Narsai et al, 2009), poplar (Populus trichocarpa; Kreuzwieser et al, 2009), Chlamydomonas reinhardtii (Mus et al, 2007), Homo sapiens (Kim et al, 2006;Chen et al, 2008;Guimbellot et al, 2009), Mus musculus (Greijer et al, 2005;Allen et al, 2006;Hu et al, 2006), Danio rerio (van der Meer et al, 2005;Marques et al, 2008), Drosophila melanogaster (Liu et al, 2006;Azad et al, 2009), Caenorhabditis elegans (Shen et al, 2005), Trichoderma reesei (Bonaccorsi et al, 2006), Saccharomyces cerevisiae (Linde et al, 1999;Lai et al, 2005;Protchenko et al, 2008), Schizosaccharomyces pombe (Todd et al, 2006), Candida albicans (Setiadi et al, 2006), Cryptococcus neoformans (Chun et al, 2007), Escherichia coli (Salmon et al, 2003;Kang et al, 2005;Covert et al, 2008), Mycobacterium tuberculosis (Park et al, 2003), Pseudomonas aeruginosa (Alvarez-Ortega and Harwood, 2007), Pseudomonas stutzeri (Dou et al, 2008), Sinorhizobium meliloti (Becker et al, 2004), Synechocystis species PCC 6803 (Summerfield et al, 2008), and Zymomonas mobilis (Yang et al, 2009). Additional Arabidopsis and human data sets evaluated responses across experimental conditions and cell types (Arabidopsis, …”
Section: Data Set Collection and Analysismentioning
confidence: 99%
“…For example, as discussed above, several reports have shown the link between upregulation of miR-23b and hypoxia [167,185,186]. As miR-23b and miR-23b* share the same precursor, miR-23b* could also be regulated by HIF.…”
Section: Mir-23b* Regulation By Other Factorsmentioning
confidence: 89%
“…A study in humans found that hypoxic events altered the expression of several miRNAs (eg, miR-152) in colonic cells. 41 An animal study screening for lung miRNA profiles in rats after chronic hypoxia showed aberrant expression of several miRNA markers, including miR-30. 42 It is possible that the aberrant expression of miRNAs might relate to hypoxic or hyperoxic insults from ventilator and oxygen use.…”
Section: Discussionmentioning
confidence: 99%